Understanding Family, Friend, and Neighbor Care in Massachusetts. - Garcia, Guadalupe; Linke, Lily; Mulligan, Danielle; Pittman, Nick; Siggers, Brooke. (Tufts University. Tisch Library., 2019)
2019 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Community Labor United.